Dynamic facial asymmetry in patients with repaired cleft lip using 4D imaging (video stereophotogrammetry). Issue 1 (January 2017) - Hallac, Rami R.; Feng, Jennifer; Kane, Alex A.; Seaward, James R.
Abstract: Background: Unilateral cleft lip is a profoundly asymmetrical condition affecting all hard and soft tissue layers from the nose to the upper lip. Although the asymmetry is minimized through cleft lip repair, a degree of asymmetry inevitably persists. Studies investigating asymmetry in patients with cleft lip have used facial measurements, and static 2D and 3D photography. The nose/lip/mouth area, however, is rarely static in our day to day social interactions. Methods: Non-syndromic patients with cleft lip and palate, and a control group without orofacial clefts underwent 50 frames per second 4D imaging while generating facial expressions including smiling and pouting. Key landmarks were tracked throughout the expression, corrected for head movement and a motion path of each landmark was generated. Asymmetry was assessed for both extent of displacement, using Euclidean distances between frames, and the shape of the motion path using Procrustes analysis. Results: Twelve patients were compared in each group with an age range from 8 to 18. Comparing the motion path of key landmarks in the upper lip demonstrated statistically significant differences in both the magnitude and shape of motion during smiling and pouting between cleft and non-cleft groups. Conclusion: Video stereophotogrammetry of the repaired cleft lip demonstrates asymmetry of both the magnitude of motion as well as asymmetry of the path of the motion itself. This may be due to the effect of the scar tissue from the repair, from the abnormal anatomy involved with cleft lip or a combination of the two.